The effect of dietary omega-3 and -6 polyunsaturated fatty acids on ovine ovarian function and the pre-implantation embryo - Hughes, Jaime (2011)
There is considerable interest in the beneficial role of dietary polyunsaturated fatty acids (PUFA) on reproduction in ruminants. Detailed information regarding the mechanisms behind this beneficial effect is limited. The main objective of this thesis was to test the effects of dietary supplementation with omega-3 (n-3) or -6 (n-6) PUFA on gene expression, fatty acid (FA) composition and steroidogenesis in granulosa and theca cells and pre-implantation embryo development.